2016
DOI: 10.1007/s00330-016-4316-4
|View full text |Cite
|
Sign up to set email alerts
|

High levels of thyroid-stimulating hormone are associated with aortic wall thickness in the general population

Abstract: • Serum TSH concentrations are positively associated with aortic wall thickness. • Serum TSH concentrations are not associated with the aortic diameters. • Serum 3,5-diiodothyronine concentrations may be positively associated with aortic wall thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
1
9
0
1
Order By: Relevance
“…It has been reported that the IMT of the carotid artery in patients with hypothyroidism is higher than that in the control group and that a decrease in IMT was observed after one year of levothyroxine replacement therapy [23]. Studies have also shown that the thickness of the human thoracic aortic wall increased with the increase of serum thyroid stimulating hormone (TSH) concentration and pointed out that hypothyroidism might indicate the occurrence of aortic atherosclerosis [24]. Hyperthyroidism may manifest as elevated systolic blood pressure, venous resistance, increased cardiac output and myocardial weight, tachycardia, and atrial fibrillation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the IMT of the carotid artery in patients with hypothyroidism is higher than that in the control group and that a decrease in IMT was observed after one year of levothyroxine replacement therapy [23]. Studies have also shown that the thickness of the human thoracic aortic wall increased with the increase of serum thyroid stimulating hormone (TSH) concentration and pointed out that hypothyroidism might indicate the occurrence of aortic atherosclerosis [24]. Hyperthyroidism may manifest as elevated systolic blood pressure, venous resistance, increased cardiac output and myocardial weight, tachycardia, and atrial fibrillation [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Serum TSH concentration is a well-known predictor of cardiovascular disease in patients with subclinical hypothyroidism (1,17) and has been linked to increased risk of coronary atherosclerosis and increased arterial stiffness in euthyroid postmenopausal women (18,19) and in the general population (20).…”
Section: Discussionmentioning
confidence: 99%
“…15 Interestingly, a conclusive relation between increased AWT and coronary artery disease has not been shown. 16 The other associations of AWT are with hypothyroidism, 17 increased cerebrovascular events, 18 and possibly for diagnosis of aortitis. 19 AWT is a risk factor in aortic dissection.…”
Section: Aortic Thicknessmentioning
confidence: 99%